A GREENER APPROACH FOR THE DEGRADATION OF DYE METHYLENE BLUE BY ORGANIC ADDITIVE CATALYSED PHOTO – FENTON PROCESS - Abhilasha, Jain; Ashma, Aggarwal; Marazban, Kotwal (Journal of the Chilean Chemical Society, 2017)
Fenton and photo-Fenton processes are proven to be most promising techniques for the wastewater treatment methods. It provides an attractive method for degradation of dyes and breaks them into simple mineral form. These are cost effective and ecologically viable techniques with additional advantages of relatively simple approach, use of less hazards chemicals for the degradation and cyclic nature. Thus, it serves as a green chemical and eco-friendly pathway in reducing pollution caused by complex dye molecule and other organic compounds. Present work has been designed to investigate photochemical degradation of dye Methylene blue by photo-Fenton reaction in presence of resorcinol as an additive. Kinetic study of the reaction has been made by using spectrophotometric technique Effect of variation of various operating parameters such as pH, concentration of Fe3+ ion, dye and additive; amount of H2O2 and light intensity has also been observed. A tentative mechanism for the photo-Fenton reaction in presence of organic additive is also given.